Sketch and Literacy - Fadlillah, Anam (Universitas Muhammadiyah Jember, 2019)
Identity is known as the concept of how people come to understand themselves through the â€œworldsâ€ they participate in and how they relate to others within and outside of these worlds. However, their identity that is constructed within their figured worlds give significant impact to their literacy practices, in which their literacy event, unconsciously, showed their identity and figured worlds that they participate in. This paper investigates one post-graduate studentâ€™s literacy event, sketching, by using the concept of figured worlds, in which it focused on figuring out how the figured worlds construct her identity in her literacy practices. The data were collected by taking photographs of the literacy events and interviewing to find out her cultural life, family, and social life that construct her identity. The findings of the study showed that somebodyâ€™s literacy events have a lot of implicit meaning rather than just a product of literacy practices.